Incidence of acute rheumatic fever and chronic rheumatic heart disease, trends in deaths in the Tula region (1991—2011) - Valentina Nikolayevna Sorotskaya; D Sh Vaisman; R M Balabanova (Научно-практическая ревматология)
The paper analyzes the incidence of acute rheumatic fever (ARF) and chronic rheumatic heart disease (CRHD) and theirs outcomes in the Tula Region in 1991 to 2011. In this period, the incidence of ARF decreased to 0.002, which was much lower than Russia's rates. That of CRHD in 2011 accounted for 1.6 per 1,000 adult population, which was comparable to the values in Russia. CRHD mortality rates showed a 2.5-fold decrease. The main causes of fatal outcomes were cardiovascular disorders.